Study of number sense and mathematical problem solving for grade 7 students - Singngoen, Sarawut; Thipchart , Yuthapong (Journal for Developing the Social and Community, 2024)
This research article aims to 1) study the number sense of of the grade 7 students, 2) study the mathematical problem solving of the grade 7 students and 3) study the relationship between number sense and the mathematical problem solving the grade 7 students. The target group used in this research was a grade 7 students at Tha Khon Yang Pittayakhom School. Kantharawichai District, Maha Sarakham Province, In the second semester of the academic year 2023, 55 people. Research tools were a level of number sense quiz, a mathematical problem solving quiz, and semi-structure interviews about number sense and mathematical problem solving. Statistics for research were percentage, average, standard deviation, pearson correlation coefficient and data were presented through descriptive analytics. The results of the study revealed that: 1) The Number sense of the grade 7 students mostly at a moderate level, representing 45.45 percent. and number sense aspect the meaning of the number at a high level, representing 45.45 percent, number sense aspect the relative size of numbers and number sense aspect relative results of various operations of numbers at a moderate level, representing 47.27 percent and representing 45.45 percent respectively. 2) The mathematical problem solving of the grade 7 students mostly at mathematical problem solving is in good level, representing 45.45 percent, and 3) the relation between the number sense and mathematical problem solving is very elated. With the coefficient of relations equal to .965 and there is a positive relationship that is statistically significant at 0.01 level. And from the interviews, it was Students with a high level of number sense Be confident in answering questions Analyze problems clearly Can you tell what the problem has given you? Can tell what the problem needs to be found. which has clearly planned methods for finding answers Choose the appropriate method to solve the problem and use other methods than the original method to find the answer. Able to solve complex problems and can check answers correctly and clearly.